Profil Kemandirian Belajar Remaja Dan Implikasinya Bagi Layanan Bimbingan Konseling - Fikriyah, Arnik Agniya; Saripah, Ipah (Universitas Muhammadiyah Metro, 2023)
This research is motivated by the phenomenon that adolescents have learning independence problems as indicated by some students not confident in their abilities, still dependent on other people, having difficulty studying independently, following friends' work, some students ask for answers during tests, and lack of initiative to ask when there is learning material that has not been understood. This study aims to determine the description of adolescent learning independence. This research uses a quantitative approach and a descriptive method. The results showed that the profile of adolescent learning independence at MAN 3 Ciamis showed that 51% or as many as 49 people were in the medium category. Furthermore, 49% or as many as 47 people are in the high category. That is, in general, the proportion of students' learning independence in the moderate category is slightly more than in the high category and relatively balanced. Based on this, it is necessary to provide counseling services, namely group guidance as an alternative to increase adolescent learning independence.